Modification and Performance Evaluation of Active Solar Dryer for High Moisture Tomato Crop - Mu’azu, K.; Mahmood, A.; Inuwa, B.; Sadiq, I. G.; Shitu, M. U. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
In this study, two active solar cabinet dryers with capacity each to dry 10 kg of fresh vegetable were fabricated. The drying cabinet of the first dryer was fabricated using plywood and is refer to as unmodified dryer (UM) while the second dryer with white transparent glass and is refer to as modified dryer (MD). The performances of the two dryers in terms of total drying time, final moisture content obtained and preservation of nutritive values of the dried vegetable were investigated using tomato as sample. Ten kilogram of the sample were sliced to about 1cm and neatly arranged in the drying chamber for the drying process in a period of two days (8am-6pm). The results revealed that there was a reduction in total drying time of 2.5 hours, from 18 hours in UM to 15.5hours in MD which corresponds to reduction in moisture content (wet basis) from initial value of 92% to final moisture content of 12- 13.3%. The results further revealed that maximum drying rate of 6.9 kg/h was observed for UM dryer and 9.4 kg/h for MD both obtained within 8 hours of drying time.  The average temperature recorded in the MD was found more than the UM by about 13°C at 3.00pm. The efficiency of the MD in terms of reduction in total drying time was 13.89% higher than the UM. Proximate analysis result shows the composition of the dried tomato in the UM to be protein, 0.76%; lipids, 1.00%; vitamin E, 0.0083%; moisture content, 13.3%; ash, 0.60% and crude fiber, 1.80%. However, the composition of dried tomato in MD were protein, 0.69%; lipids, 0.90%; vitamin E, 0.0080%; moisture content, 12%; ash, 0.58% and crude fiber, 1.78%.